A heuristic approach applied to the fleet sizing problem for military ground vehicles. Issue 1 (10th December 2020) - Longhorn, Dave C.; Stobbs, John Dale
Abstract : Purpose: This paper aims to propose two solution approaches to determine the number of ground transport vehicles that are required to ensure the on-time delivery of military equipment between origin and destination node pairs in some geographic region, which is an important logistics problem at the US Transportation Command. Design/methodology/approach: The author uses a mathematical program and a traditional heuristic to provide optimal and near-optimal solutions, respectively. The author also compares the approaches for random, small-scale problems to assess the quality and computational efficiency of the heuristic solution, and also uses the heuristic to solve a notional, large-scale problem typical of real problems. Findings: This work helps analysts identify how many ground transport vehicles are needed to meet cargo delivery requirements in any military theater of operation. Research limitations/implications: This research assumes all problem data is deterministic, so it does not capture variations in requirements or transit times between nodes. Practical implications: This work provides prescriptive details to military analysts and decision-makers in a timely manner. Prior to this work, insights for this type of problem were generated using time-consuming simulation taking about a week and often involving trial-and-error. Originality/value: This research provides new methods to solve an important logistics problem. The heuristic presented in this paper was recently used to provide operational insights about ground vehicle requirements to support a geographic combatant command and to inform decisions for railcar recapitalization within the US Army.